Unveiling Optimal Conditions for Phenol Degradation: Response Surface Methodology and ANOVA Analysis of ZnO and Ag-Doped ZnO Photocatalysts - Mohan, G.; Meenachi, S.; Kiruthika, K.; Kirthiga, D. (Nature environment and pollution technology, 2025)
This research explores the effectiveness of ZnO and Ag-doped ZnO photocatalysts in degrading organic pollutants, specifically focusing on phenol removal in wastewater treatment. The catalysts were synthesized using sol-gel and precipitation methods and characterized through XRD, SEM, and EDX analyses. The study assessed the degradation efficiency of phenol under various conditions, including different catalyst dosages, irradiation times, and initial phenol concentrations. UV-vis spectroscopy was used to measure degradation efficiency, revealing significant differences between the two catalysts. Ag-doped ZnO showed superior performance, achieving degradation efficiencies of over 90%, compared to ZnO’s 60-70%. Statistical analyses, including ANOVA and Response Surface Methodology (RSM), identified key factors influencing degradation efficiency. The enhanced performance of Ag-doped ZnO was attributed to its narrower band gap energy and improved irradiation responsiveness. These findings indicate that Ag-doped ZnO is a promising candidate for efficient and sustainable wastewater treatment, offering a robust solution for removing organic impurities and supporting environmental preservation. This research provides valuable insights into advanced photocatalytic processes and sets the stage for future wastewater treatment innovations.